Efficient motion vector selection and mode decision schemes for transcoder between DVC and VC-1 - Lee, Jae-Yung; Han, Jong-Ki; Sim, Dong-Gyu (IEEE transactions on consumer electronics, 2012)
Transcoding between Distributed Video Coding (DVC) and VC-1 is an interesting research topic, has various applications, and VC-1 is one of most popular and efficient video codecs. Among the various techniques related to transcoders, we focus on motion estimation and mode decision. In this paper, we propose a Best Matched Vector Selection (BMVS) and fast mode decision to increase the accuracy and speed of the motion vector estimation and mode decision in the transcoder. BMVS is used to predict motion vectors for multiple reference frames that are far from the current frame. The proposed mode decision scheme selects a mode for the current coding block based on the information transferred from the DVC decoder, without calculating the Rate-Distortion (RD) costs for all possible candidate modes. Simulation results show that the proposed schemes simplify the transcoder significantly without degrading the transcoded video sequences.